WORKSHOP PENDAMPINGAN BISNIS TEKNOLOGI CERDAS “SMART TRASH BIN” DESA KESAMBEN, KECAMATAN NGAJUM, MALANG, INDONESIA - Dura, Justita; Cahyaningtyas, Fadilla; Yogatama, Ahmad Nizar; Bukhori, Mohammad; Hanif, Rifki; Aqromi , Nur Lailatul; Afiyah, Siti Nurul; Riska, Suastika Yulia; Farokah, Lia; Arifin, Jaenal; Islamiyah, Mufidatul; Arifin, Samsul; Jatmika, Sunu (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Kesamben Village, Ngajum District, Malang Regency faces serious problems in waste management that have an impact on the environment and public health. This community service program aims to introduce "Smart Trash Bin" technology as an innovative solution in improving the efficiency and effectiveness of waste management in the village. This technology uses automatic sensors that allow people to dispose of garbage without touching the trash can, making it more hygienic and comfortable. Early results show high enthusiasm from the public for this technology, which can be seen from active participation in socialization, training, and question and answer sessions. The application of this technology has also succeeded in improving environmental cleanliness and reducing health risks. However, some challenges such as high implementation costs and difficulties in technology adaptation still need to be overcome through adequate financial support and ongoing training. With collaboration between the government, local communities, and related parties, this program has great potential to become a model in the application of smart technology for sustainable waste management in other regions.